Scammell, C. (2018). Translation strategies in global news: What Sarkozy said in the suburbs. Cham: Palgrave Macmillan. 98 pp. - Li, Xiangdong (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
Book review